PERAN PEMUDA DALAM PENGELOLAAN PARIWISATA PANTAI AIA BANGIH KENAGARIAN AIA BANGIH KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - -, Oktavianti - (Pendidikan Sosiologi, 2014)
The background of this research because of the occurrence of deviant behavior when Bangih Aia beach frequented by visitors, especially among teenagers who came with her partner, in this case they act things that are not in accordance with the values and norms, that is, they do immoral, fighting, and also drinking. This study aimed to describe the role of youth in tourism management Bangih Kenagarian Aia Aia beach Bangih Beremas River District West Pasaman.theory used is structural functionalism developed by Robert K. Merton, the research approach is qualitative approaches, which approaches that attempt to explain social reality to be observed in depth and use of qualitative data in the form of words and deeds. the selection of informants in this study using purposive sampling technique which amounts to 10 informants study. data collection techniques used were observation, interview. the unit of analysis is the group. analysis of the data used includes 4 stages: 1) data collection, 2) data reduction, 3) presentation of data, 4) and conclusion. This research conducted at the location of Aia Kenagarian Bangih Beremas River District West Pasaman.based on the results obtained the following conclusions: the role of youth in tourism management Aia beach Bangih among others: 1) the role of youth in protecting the security of: a) so that visitors do not commit adultery, b) so that visitors do not fight, c) so as not drinking alcohol , d) and maintain the safety of visitors. 2) the role of youth in maintaining order: a) in the distribution of tickets, b) regulate parking, c) set the path to the beach area. 3) the role of youth in maintaining the cleanliness of the beaches along the way youth do goro in 1 x in a month.